Sparfloxacin Crystals And Pharmaceutical Salts Containing Dicarboxylic Acid: Increasing Sparfloxacin's Solubility And Permeability To Enhance Its In-Vitro Antimicrobial Activity (International Journal of Food and Nutritional Sciences, 2022)
Two new pharmaceutical salts/cocrystals of sparfloxacin (SPX) with oxalic acid and malonic acid have been designed, synthesized, and characterized to enhance its antimicrobial activity in vitro. The current research showed the co crystalalization of sparfloxacin with oxalic acid and malonic acid (SPX-OXA and SPX-MLO). The FTIR and XRD confirm the stable formation of target compound. Thermal analysis showed the water loss during the production of these co crystals. The crystal exhibit considerable antimicrobial activity against Escherichia.coli, Staphylococcus. aureus and Candida albicans as compared to sparfloxacin alone. This suggests that oxalic acid and malonic acid-prepared pharmaceutical salts or cocrystals of Spx can boost antibacterial action and improve solubility and permeability.